Study on Numerical Simulation of Seismic Collapse of RC Frame Structure with Infilled Wall - Defeng Xu; Junwu Dai; Yongqiang Yang; Xuran Weng; Gang Sun (Advances in Civil Engineering)
The infilled wall plays an important role in the formation of the survival space and life-saving passage of the seismic collapse of reinforcement concrete (RC) frame structure. Here, with the numerical modeling method of the infilled wall, the connection between infilled wall and RC frame was primarily investigated. The combined finite element (FE) and finite-discrete element (F-DE) method is proposed to simulate the multispan and multistory RC frame structure with infilled wall. The reliability of the numerical simulation method was verified by the shaking table test; the evaluation criterion includes the collapse mechanism and mode. The results show that the numerical simulation is highly consistent with the shaking table test; it is easy for RC frame structure to form short columns due to the influence of the low or half-height infilled wall, and the structural collapse is caused by the shear failure of columns; the overall structure shows pancake type of collapse; the survival space becomes smaller and smaller on the direction of structural collapse. The proposed numerical simulation method can be valuable in simulating RC frame structure with infilled wall for postearthquake rescue.